Decentralizing Eligibility for a Federal Antipoverty Program - Ravallion, Martin (World Bank, 2012)
In theory, the informational advantage of decentralizing the eligibility criteria for a federal antipoverty program could come at a large cost to the program's performance in reaching the poor nationally. Whether this happens in practice depends on the size of the local-income effect on the eligibility cutoffs. China's Di Bao program provides a case study. Poorer municipalities adopt systematically lower thresholds—roughly negating intercity differences in need for the program and generating considerable horizontal inequity, so that poor families in rich cities fare better. The income effect is not strong enough to undermine the program's overall poverty impact; other factors, including incomplete coverage of those eligible, appear to matter more.